2004
DOI: 10.1300/j003v18n01_03
|View full text |Cite
|
Sign up to set email alerts
|

An Exploratory Study of Web-Based Supports for Occupational Therapy Students During Level II Fieldwork

Abstract: Occupational therapy students often experience high levels of anxiety about transitioning from the academic student role to the fieldwork student role. The separation from their classmates and the geographical relocation may isolate some students. Additionally, the quality and quantity of on-site supports available to individual students vary with each placement.A web-based resource was designed to assist occupational therapy students from the University of South Alabama with the transition from student role i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…Previous research that have been conducted within the OT profession has focused on using e-learning technologies to augment level II clinical rotations [2126], which typically occur at the end of a student's courses of study.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research that have been conducted within the OT profession has focused on using e-learning technologies to augment level II clinical rotations [2126], which typically occur at the end of a student's courses of study.…”
Section: Discussionmentioning
confidence: 99%
“…Penmann and Cheetham (2007) researched the use of mobile phones and online discussion boards for students on practical placements and found that they provided useful communication tools to keep students engaged and supported by one another whilst on placement, particularly in rural areas. Wooster (2004) found that discussion boards assisted students in remote regions to seek resources from staff and students. This study also found that whilst no grades were attached to the discussion boards, students chose to access these resources in order to independently seek information and develop their skills whilst off campus.…”
Section: Introductionmentioning
confidence: 99%
“…As we come to understand more about the processes and elements of clinical reasoning, and as services users continue to take up opportunities to be included in the clinical reasoning process, the process of teaching clinical reasoning becomes more demanding (Higgs & Jones, 2008; Ryan & Higgs, 2008; Schell & Schell, 2008a). A number of authors have described the potential benefits of online interactions to support the development of a range of skills, including clinical reasoning (Creel, 2001; Hollis & Madill, 2006; Murphy, 2004; Thomas & Storr, 2005; Wooster, 2004).…”
Section: Introductionmentioning
confidence: 99%